Prospects for the introduction of the concept of TQM (Total Quality Management) in higher educational institutions of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
The article analyzes the implementation of the requirements of the concept of total quality management in higher educational institutions of Uzbekistan.